Coupling Between Colloidal Assemblies Can Drive a Bistable‐to‐Oscillatory Transition. Issue 3 (7th November 2019) - Sánchez‐Farrán, María Antonieta; Borhan, Ali; Sen, Ayusman; Crespi, Vincent H.
Abstract: We present a model to describe oscillations and collective behavior in a heterogeneous system of active colloidal clusters whose motility and interactions are driven by an oscillatory chemical reaction, as motivated by experimental observations of collective behavior in silver phosphate clusters under UV light in the presence of hydrogen peroxide, where spatio‐temporal correlations in cluster behavior are presumably modulated by diffusive communication between clusters. A generic model for a single bistable cluster becomes oscillatory upon introduction of inter‐cluster interactions that relate to localized emission or consumption of diffusing species. Multi‐cluster simulations capture the qualitative features in the experimentally observed spatio‐temporal correlations in the oscillations of nearby clusters. Since the model is generic and does not rely upon a particular chemical mechanism, it can be applied to other active matter systems exhibiting collective behavior, where interactions between bistable entities can drive collective oscillations. Abstract : Modeling collective phenomena in colloidal assemblies : Active colloidal clusters display collective behavior, where spatio‐temporal correlations in cluster behavior are likely driven by diffusive communication between clusters. In a simplified and generic non‐linear model, we show that interactions between clusters that are otherwise chemically bistable lead to oscillations and spatio‐temporal correlations in cluster behavior. The model captures the qualitative features that silver phosphate and silver chloride assemblies exhibit inthe presence of hydrogen peroxide and UV illumination.